1991
DOI: 10.2307/2135777
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Family Planning Services Among Patients in Drug Treatment Programs

Abstract: In July 1989, family planning services were integrated into 13 drug treatment programs in Philadelphia. To obtain information on the family planning needs of women in drug treatment programs, baseline interviews were conducted with 599 women. Three-quarters of these women had had a sexually transmitted disease, and although they were in a drug treatment program, 41 percent had injected drugs in the previous month. In addition, 62 percent of the women who were sexually active in the previous month had not used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
53
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 5 publications
4
53
0
Order By: Relevance
“…5 A few studies have explored women's experiences with discrimination while receiving reproductive health care, 6,[11][12][13] but none has specifically examined women's experiences of discrimination while receiving prenatal or obstetric care. We assessed perceptions of discrimination during prenatal care, labor, and delivery among Oregon women.…”
mentioning
confidence: 99%
“…5 A few studies have explored women's experiences with discrimination while receiving reproductive health care, 6,[11][12][13] but none has specifically examined women's experiences of discrimination while receiving prenatal or obstetric care. We assessed perceptions of discrimination during prenatal care, labor, and delivery among Oregon women.…”
mentioning
confidence: 99%
“…Their decision is compounded by the finding that physicians are less likely to prescribe a Highly Active Antiretroviral Therapy (HAART) if a woman has an alcohol problem, uses drugs intravenously, or has a mental illness [13] and thus the women are more likely to have high viral loads [14]. Armstrong et al [15] reported that women in focus groups shared that clinicians had called them "junkies" and "crack ladies" and therefore were reluctant to seek treatment at a regular prenatal care. One woman said "In a place like (a High Risk Clinic)…you don't have to live a double life".…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 99%
“…Other barriers these women face in accessing contraception include a belief that contraception is not needed due to impaired fertility while in drug treatment (e.g. methadone) and misinformation about different methods [4]. As it stands currently, women in specialist drug treatment needing sexual and reproductive health care are usually referred to external services, either to their general practitioners, sexual health clinics or family planning centres.…”
mentioning
confidence: 99%
“…For example, integrated care models are more effective in enhancing health-care utilization (e.g. hepatitis B virus vaccination and hepatitis C virus treatment) in drug treatment populations, and we hope to trial an integrated contraceptive service, as suggested by previous work with drug treatment populations in the United States [4].Any discussion of the ethical issues of providing financial or other incentives for women to utilize effective contraception must take into consideration the extent bs_bs_banner Letters to the Editor 1361 …”
mentioning
confidence: 99%